Advanced production technology yields more flowers - Dutt, Som (Indian Horticulture, 2019)
One-day workshop on Advanced Production Technology of Flower Crops, was organized under AICRP on Floriculture, at ASPEE College of Horticulture and Forestry, NAU, Navsari, in collaboration with KVK, Navsari, on 16 January 2018 at Swami Vivekanand Hall, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, for flower growers. The inaugural session was presided upon by Dr C J Dangaria, Vice-Chancellor, NAU, Navsari. Dr K V Prasad, Director, ICARDFR, Pune, graced the function as a Chief Guest. Dr S R Chaudhary, Director of Research and Dean, PGS and Dr G R Patel, Director of Extension Education, NAU, Navsari, were special guests. Dr B N Patel, Principal and Dean, ACHF; Dr P K Shrivastava, Principal, College of Forestry; Dr C K Timbadia, Programme Co-ordinator, KVK, NAU and Head of various departments, faculties of ACHF, PG students and 146 farmers attended the event.